Integrasi Penelitian, Praktik Tasawuf, Inovasi Digital, dan Kesehatan Mental dalam Pendidikan Islam Kontemporer - Sadam; Nasrulloh (Al-Kindi, 2026)
This study explores the integration of Sufi values within Islamic psychotherapy as a holistic framework for addressing students’ mental health issues in the digital era. The rapid development of technology has created psychological pressures such as digital anxiety, emotional instability, and social comparison, which significantly affect students’ well-being. Through a qualitative descriptive approach based on library research, this study analyzes core Sufi concepts including muhasabah, dzikr, sabr, tawakkul, and tazkiyah al-nafs, and examines their relevance to emotional regulation, cognitive balance, and spiritual resilience. The findings indicate that Sufi practices provide effective mechanisms for reducing stress, enhancing self-control, and shaping inner peace. Furthermore, integrating these values with Islamic psychotherapy offers a more comprehensive therapeutic approach by aligning cognitive, emotional, and spiritual dimensions. This integration leads to the development of the Integrated Sufi-Based Islamic Psychotherapy Model, which emphasizes the stages of takhalli, tahalli, and tajalli as practical strategies for building students’ mental strength and spiritual identity. Overall, the study contributes to the advancement of Islamic mental health discourse and provides practical recommendations for educators and counselors to implement spiritually grounded interventions in educational settings.